IMPLEMENTATION OF TEACHING AND LEARNING APPROACHES IN TASKA TO FULFIL PARENTS’ ASPIRATIONS: A STUDY IN TEMERLOH - NOR AFIFAH ZAHIRA MOHD RAHIMI; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This research investigated how teaching and learning practices used in early childhood care centres (TASKA) in Temerloh effectively respond to parents’ aspirations. The research is qualitative in nature, containing data from interviews with two TASKA teachers, as well as library research to generate information on current teaching practices and parental expectations. The results indicate that both teachers value holistic development through play-based learning, visual aids, and teaching self-help skills. Parents’ hopes for their children focus on physical, social, emotional, and cognitive development. Other important influences on teacher practice included ongoing teacher education, parents involvement, and quality resources. The study indicates the significance of teacher-parent collaboration in terms of supporting effective, quality learning experiences for infants and toddlers.